New Results on Combined Audio Compression/Watermarking - Siebenhaar, Frank; Neubauer, Christian; Herre, Jürgen; Kulessa, Ralph (111th AES Convention, 2001)
Today, music distribution over the Internet is an increasingly important business. In this context, watermarking can provide beneficial means to transmit rights information within the content. To convey the origin of such content, the combination of simultaneous low bit rate encoding and watermark embedding is a promising novel technique. This paper describes the basic concept of combined compression/watermarking for audio signals. In contrast to separate steps of encoding and watermarking the combined approach enables an optimal coordination between the quantization strategy in the audio encoder and the watermark embedding process. This allows to adjust the system to specific needs in terms of audio quality and watermark robustness. Experimental results obtained from an extended MPEG-2/4 AAC encoder and a first implementation of an extended MPEG-1/2 Layer-3 encoder confirm the potential of the concept.<br
herre_papers_audio_watermarking
Keywords: Loudspeakers; Watermarking